Β2-adrenergic Agonists Rescue Lysosome Acidification and Function in PSEN1 Deficiency by Reversing Defective ER-to-lysosome Delivery of ClC-7. Issue 8 (3rd April 2020) - Lee, Ju-Hyun; Wolfe, Devin M.; Darji, Sandipkumar; McBrayer, Mary Kate; Colacurcio, Daniel J.; Kumar, Asok; Stavrides, Philip; Mohan, Panaiyur S.; Nixon, Ralph A.
Abstract: Lysosomal dysfunction is considered pathogenic in Alzheimer disease (AD). Loss of presenilin-1 (PSEN1) function causing AD impedes acidification via defective vacuolar ATPase (vATPase) V0a1 subunit delivery to lysosomes. We report that isoproterenol (ISO) and related β2-adrenergic agonists reacidify lysosomes in PSEN1 Knock out (KO) cells and fibroblasts from PSEN1 familial AD patients, which restores lysosomal proteolysis, calcium homeostasis, and normal autophagy flux. We identify a novel rescue mechanism involving Portein Kinase A (PKA)-mediated facilitation of chloride channel-7 (ClC-7) delivery to lysosomes which reverses markedly lowered chloride (Cl − ) content in PSEN1 KO lysosomes. Notably, PSEN1 loss of function impedes Endoplasmic Reticulum (ER)-to-lysosome delivery of ClC-7. Transcriptomics of PSEN1 -deficient cells reveals strongly downregulated ER-to-lysosome transport pathways and reversibility by ISO, thus accounting for lysosomal Cl − deficits that compound pH elevation due to deficient vATPase and its rescue by β2-adrenergic agonists. Our findings uncover a broadened PSEN1 role in lysosomal ion homeostasis and novel pH modulation of lysosomes through β2-adrenergic regulation of ClC-7, which can potentially be modulated therapeutically. Graphical abstract: Image 1 Highlights: β2-AR agonists restore normal lysosome acidity and function in PSEN1 -FAD cells. ER export of ClC-7 and delivery to lysosomes require PSEN1. Deficient lysosomal ClC-7 and vATPase in PSEN1 KO together elevate lysosomal pH. β2-AR-PKA signaling boosts lowered ER export gene transcription and ClC-7 delivery.